2021
DOI: 10.1161/hypertensionaha.120.16249
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness, Central Blood Pressure, and Pulsatile Arterial Load Predict Future Thoracic Aortic Aneurysm Expansion

Abstract: Thoracic aortic aneurysm is a disease associated with high morbidity and mortality. Clinically useful strategies for medical management of thoracic aortic aneurysm are critically needed. To address this need, we sought to determine the role of aortic stiffness and pulsatile arterial load on future aneurysm expansion. One hundred five consecutive, unoperated subjects with thoracic aortic aneurysm were recruited and prospectively followed. By combining arterial tonometry with echocardiography, we estimated measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…The literature survey was carried out with emphasis on diseases reported to be associated with vascular stiffening: congenital heart disease (CHD) [ 19 ], thoracic aortic aneurysm (TAA) [ 20 , 21 ], and hypertension [ 17 , 18 ]. We utilized the PubMed database, as well as Google Scholar, in order to select the source literature containing candidate genes or loci with mutations to be analyzed regarding each disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature survey was carried out with emphasis on diseases reported to be associated with vascular stiffening: congenital heart disease (CHD) [ 19 ], thoracic aortic aneurysm (TAA) [ 20 , 21 ], and hypertension [ 17 , 18 ]. We utilized the PubMed database, as well as Google Scholar, in order to select the source literature containing candidate genes or loci with mutations to be analyzed regarding each disease.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial stiffening, an independent predictor of cardiovascular morbidity and mortality, plays an important role in cardiovascular diseases (CVDs) [ 15 , 16 ], including hypertension [ 17 , 18 ], congenital heart disease (CHD) [ 19 ], and thoracic aortic aneurysms (TAA) [ 20 , 21 ]. Given the multigenic causes of these conditions, elucidation of the genetic characteristics or factors impacting high mutation rates might reduce the burden of high mortalities [ 22 ] in these CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the natural history of arterial aging, elastin gradually breaks down without compensatory replacement, and collagen fibers become the predominant mechanical bearing unit of the aortic wall (23,25). The result is an overall stiffening of arteries that is itself an independent predictor of aortic dilatation and the need for aortic surgery (26)(27)(28), as well as a key driver of aortopathy pathogenesis (29)(30)(31)(32). Our data suggest that the mechanical properties of the older patients follow this aging effect with a stiffening associated with elastin breakdown occurring in both the low-strain (LTM) and high-strain regions (HTM).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of aortic stiffness, such as pulse wave velocity (PWV), have been shown to be independently associated with future thoracic aortic aneurysm expansion [73]. Several studies have reported that patients with PA have increased arterial stiffness, as indicated by higher values of PWV and augmentation index (AIx) as compared with patients with EH with comparable blood pressure levels [74,75].…”
Section: Primary Aldosteronism and Aortic Ectasiamentioning
confidence: 99%